The Effectiveness of Kahoot! in Improving Understanding of Scientific Works in the Distance Learning - Alimatussa’diyah; Candra Oktyasari Putri; Okpina Rochadian; Pangkat Mondiana S; Ericka Ratna N (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The Covid-19 virus pandemic that has hit the world since two years ago has changed the education system rapidly and extremely, mainly in the process of teaching and learning activities. All learning activities turn into distance learning. This research tries to study the students of Semarang Polymarine in the Commercial and Port Shipping Management Study Program who take an Indonesian language course. It has two main objectives. The first is to improve the students' ability to write scientific papers on distance learning. The second one is to find out the effectiveness of using Kahoot! to improve the ability to write scientific papers on distance learning. This is a classroom action research that consists of two cycles each research stage to identify and view the implementation of the Kahoot! in the learning process. Each cycle is divided into four stages of research. They are planning, implementation, observation, and reflection. This research uses three techniques in data collection, namely observation, interviews, and documentation. The results show that there is an increase in the students’ learning outcomes which can be seen from the post-test scores. The use of Kahoot! can also be said as successful, because the students’ learning outcomes have reached 75% of the students’ being tested